ENHANCING PARENTS’ PEDAGOGICAL CULTURE: A DISCOURSE ON METHODOLOGICAL SUPPORT - S. T. Azimova (Innovate Conferences, 2025)
This article analyzes the essence and content of the process of enhancing parents’ pedagogical culture, as well as its role and significance in the modern education system.
Keywords: parental pedagogical culture, methodological support, family–school cooperation, educational (upbringing) competence, pedagogical technologies, psychological literacy, interactive methods, innovative approaches, pedagogical discourse, family upbringing, communication culture, pedagogical collaboration, digital pedagogy, educational process.